Trade globalization and political liberalization: A gravity approach - Miaojie Yu (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
The literature has paid very little attention to a potential positive endogenous nexus between trade globalization and political liberalization. In this paper, I apply a structural approach to investigate two-way causality between the two based on the gravity trade theory, using data from a sample of 134 IMF countries over the pe- riod 1974-1998. An extensive search shows that trade globalization dampens political liberalization, though political liberalization fosters trade globalization. The paper also presents ample evidence of simultaneous bias when such bidirectional causality is ignored. Finally, it contains a thorough exploration of parameter heterogeneity by income and by region.
Keywords: F13; P16; 330; Trade; Democracy; Gravity Equation; Internationale Wirtschaft; Globalisierung; Demokratisierung; Gravitationsmodell; Theorie; Schätzung; Welt